LUKISAN DALAM PANDANGAN IMAM HAMBALI - Nasikhah, Atik Dina; dinanasikhah, atik (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2025)
According to Islam, art is guiding humans towards monotheism and devotion to Allah SWT. Art formation aims to produce good and civilized humans. It is hoped that art will have motifs that depict goodness so that it can be a means of supporting a positive educational process, but it must be in accordance with the limitations that exist in Islamic law and the source of Islamic law, namely the Al-Qur'an, which provides inspiration for Muslims to develop art from the Prophet to now, then what is the opinion of the ijma' ulama, especially Imam Hanafi, in responding to art or paintings? Is Imam Hanafi's opinion about art the same as that taught by Islam and its legal sources? If it is not the same then what about art or painting according to Imam Hambali's view? Research in this journal uses library research, namely studies that study various reference books and the results of previous and similar research which are useful for obtaining a theoretical basis for the problem to be researched. Data collection uses paraphrasing. The results of this research are that paintings are permissible from an Islamic point of view, but among Ulama or Madzhab Imams, especially Hambali Imams, it is haram or referred to as Murtakib al Kabir (major sin) if the painting is used for worship, and the painting is in the form of an animate creature. Meanwhile, there are those who allow painting on clothes and those who forbid it.